The Propeller Concept Applied to Free Flaps and the Proposal of a “Clock Flap” Nomenclature - Antonini, Andrea; Rossello, Carlo; Salomone, Carlo; Carrega, Giuliana; Felli, Lamberto; Burastero, Giorgio (Journal of Reconstructive Microsurgery, 2017)
Background It is a common experience for reconstructive surgeons to feel the necessity for large flaps and minimal donor-site morbidity at the same time. In the reported cases where we felt this call intraoperatively, we have met our need by applying the “propeller concept” to fasciocutaneous or composite flaps, separating and rotating its different tissue components.Methods We present a series of five cases in which we separated and rotated diversely fascial and cutaneous components of free perforator flaps to enhance the extension of the flap or to tailor it better on the tissue gap for optimal functional and aesthetic results. We also propose a simple nomenclature system for rotation angles' definition, summarized as the “clock flap” classification, where the different components of the flap represent the arms of a clock which has the main vessel axis on the 12–6 line.Results All reconstructive procedures succeeded with only minor complications. No partial failure due to vessel rotations was noticed.Conclusion Applying “propeller style” rotations to different components of free flaps seems to be a safe procedure which may help maximize flap performance in terms of coverage of the recipient site, while minimizing scars and impairment of the donor site. Also, the proposed nomenclature gives the opportunity to record and compare surgical procedures for statistical analysis.
Keywords: free flap; propeller; clock flap